“Sistema de control interno en la gestión operativa de la empresa zamarino s.a. año 2019” - Velasco Angulo, Cecilia Esther (2021)
This research work consists of the evaluation of the Internal Control System in the operational management of ZAMARINO S.A. port cargo operating company during 2019, has a mixed approach, non-experimental type and descriptive scope that allowed to analyze the results obtained after applying an interview to the manager and surveys of 11 employees. Among the findings found, it can be mentioned that there are no evaluation reports on the operational management of the company, it does not have internal policies, established objectives, or physical evidence of the control procedures. In addition, after applying the questionnaire to evaluate the internal control process made up of its five environments: Control, Risk Assessment, Control Activities, Information and Communication, and Supervision and Follow-up. It was evidenced that the confidence level of the company is moderate and the risk level is low. These findings can impact on the good practices of the company to achieve the goals and profitability for its growth and future development. Therefore, it is concluded that it is necessary to create internal policies, objectives and procedures for the reasonable efficiency and security of the company's operations and the good performance of the personnel during the provision of services to its clients. Keywords: Internal Control, COSO, operational management, confidence level